2020
DOI: 10.3390/cancers13010106
|View full text |Cite
|
Sign up to set email alerts
|

There Are No Differences in Positive Surgical Margin Rates or Biochemical Failure–Free Survival among Patients Receiving Open, Laparoscopic, or Robotic Radical Prostatectomy: A Nationwide Cohort Study from the National Cancer Database

Abstract: Purpose: To estimate the rates of positive surgical margin (PSM) and biochemical failure–free survival (BFS) among patients with prostate cancer (PC) receiving open, laparoscopic, or robotic radical prostatectomy (RP). Patients and Methods: The patients were men enrolled in the Taiwan Cancer Registry diagnosed as having PC without distant metastasis who received RP. After adjustment for confounders, logistic regression was used to model the risk of PSM following RP. After adjustment for confounders, Cox propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“… 17 The TCRD of the Collaboration Center of Health Information Application contains detailed patient information, such as clinical stage, pathological stage, surgical margin status, surgical procedures, treatment techniques, radiotherapy, chemotherapy regimens, and follow-up visits. 5 , 6 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Our protocols were reviewed and approved by the institutional review board of Tzu-Chi Medical Foundation. Patient consent was waived because data files are deidentified by scrambling the identification codes of both patients and medical facilities and sent to the National Health Research Institutes to form the original files of NHIRD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 The TCRD of the Collaboration Center of Health Information Application contains detailed patient information, such as clinical stage, pathological stage, surgical margin status, surgical procedures, treatment techniques, radiotherapy, chemotherapy regimens, and follow-up visits. 5 , 6 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Our protocols were reviewed and approved by the institutional review board of Tzu-Chi Medical Foundation. Patient consent was waived because data files are deidentified by scrambling the identification codes of both patients and medical facilities and sent to the National Health Research Institutes to form the original files of NHIRD.…”
Section: Methodsmentioning
confidence: 99%
“… 5 , 6 Currently, 3 common surgery options are available: robot-assisted RP (RARP), laparoscopic RP (LRP), and traditional open RP (ORP). 5 , 6 , 7 , 8 , 9 , 10 , 11 Few studies have compared empirical perioperative and postoperative outcomes of these RP types for patients with PC. 12 , 13 , 14 Strong evidence is lacking for concluding which of the 3 surgery types has the fewest acute and chronic surgical complications.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the Taiwan Cancer Registry Administration often randomly reviews charts and interviews patients to verify diagnosis accuracy, and hospitals with outlier chargers or practices may be audited and heavily penalized if malpractice or discrepancies are identified. Third, RP techniques are improving with the development of open, laparoscopic, and robotic methods [21]. Modern surgical techniques were not analyzed in our study.…”
Section: Discussionmentioning
confidence: 95%
“…The Death Registry data are additionally linked to the NHIRD to verify the cause of death and vital status of each patient. The TCRD contains detailed information, such as AJCC stages, surgical procedures, techniques, RT, hormone treatments, and pathologic stages [19][20][21][22][23][24][25][26].…”
Section: Databasementioning
confidence: 99%
“…Chang et al [2] reported the difference in oncologic outcomes among prostatectomy modalities, such as open, laparoscopic, and robotic surgeries, using the National Cancer Database in Taiwan. They found no significant differences in the positive surgical margin and biochemical recurrence rate among patients who underwent open, laparoscopic, or robot-assisted radical prostatectomy after propensity score adjustment.…”
mentioning
confidence: 99%